Brief Documentation of Basidiomycota and Ascomycota Diversity in Gunung Gading National Park, Sarawak - Mohamad Bukhori, Mohamad Fhaizal; Besar, Ketol; Khairil Rizadh, Razali; Azizi, Hussain; Mohd Faizullah, Rohmon (Universiti Pendidikan Sultan Idris, 2019)
To facilitate the learning objectives of ecology, biodiversity and environment course, in situ activities remain the finest key to complement by conducting real fieldwork and hands on study. The specific objectives of the study are to promote sustainable learning, adopting effective practice in academic and scientific documentation, and implementing holistic and blended learning approach in the course by introducing a comprehensive learning experience in biodiversity-related discipline. Therefore, Basidiomycota and Ascomycota study based on diversity, host association and community structure in Gunung Gading National Park was chosen and resulted with the following attributes, where, four different species of macrofungi were identified and classified including Ganoderma, Coprinellus and Cookeina. Information on Basidiomycota and Ascomycota diversity species present in the parks is useful for educational and research purposes such as in Malaysian fungal diversity, climate change marker and Malaysian fungal monograph, developing a conservation education and attitude towards scientific reporting and also helps in promoting ecotourism.